Respon Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) terhadap Pemberian Dosis Pupuk Kandang Kotoran Itik pada Lahan Rawa Lebak - Noraida Hayati (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2012)
Mustard greens is a vegetable commodity that has high economic value and contains vitamins A, B and C. The growth and production of mustard greens in swampy swamps can be optimal if the addition of fertilizer is done with organic or non-organic fertilizers. Duck manure contains macro and micro nutrients which are high enough to support the growth of mustard greens. This study aims to (i) determine the growth response and yield of mustard greens to the administration of several doses of duck manure in lebak swamp land (ii) obtain the best dosage of duck manure that can respond to growth and yield of mustard plants on lebak lowland. This research was conducted in Sungai Durait Village, Babirik District, Hulu Sungai Utara Regency. In July - August 2008, using a single randomized block design (RBD), with 6 treatments and 4 replications so that there were 24 experimental units. Examinee factor is dosage duck's manure that is 0 kg.m2, 0,5 kg.m2, 1 kg.m2, 1,5 kg.m2, 2 kg.m2, 2.5 kg.m2. The result of the research showing the treatment duck's manure very significant response to all of variable with the best treatment is 1,5 kg.m2 or 15 ton.ha-1